Brand Loyalty and Customer Citizenship Behavior Among Students of Selected Universities Within Mount Kenya Region - MOYWAYWA, ANNE (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Enrollment in Kenya’ public universities has been declining. This study seeks to determine the effect of brand loyalty on customer citizenship behavior among students of selected universities within Mount Kenya region. The study is anchored on Keller brand theory. The study adopted a descriptive research survey. The accessible target population was 3000 4th year students of selected universities within Mount Kenya region. The study used sampling formula proposed by Israel (2009) to obtain the required sample size of 254 respondents from the study. Primary data was collected using both closed and open-ended questionnaires. The questionnaires were carefully structured and pre-tested and adjusted to meet the demands of the study. Data was analyzed using descriptive and inferential statistics. According to correlation outcome, brand loyalty had a strong positive and significant correlation with customer citizenship behavior (r =0.658, p=0.000). Regression findings showed that brand loyalty had a positive and significant effect on customer citizenship behavior (β=0.174, p=0.002<0.05). The study concluded that brand loyalty contributes significantly to enhanced customer citizenship behavior. The university management should create brand loyalty of the university by ensuring that they offer quality education which can enhance competitiveness and thus increase the number of students enrolling in the universities.